Financial barriers to structural change in developing economies: A theoretical framework - Giuliano Toshiro Yajima; Lorenzo Nalin (Levy Economics Institute of Bard College, 2022)
Liabilities denominated in foreign currency have established a permanent role on emerging market firms' balance sheets, which implies that changes in both global liquidity conditions and in the value of the currency may have a long-lasting effect for them. In order to consider the financial conditions that may encourage (discourage) structural change in a small, open economy, we adopt the framework put forward by the "monetary theory of distribution" (MTD). More specifically, we follow the formulation adopted by Dvoskin and Feldman (2019), whereby the financial system is intended as a basic sector that promotes innovation (Schumpeter 1911). In accordance with this, financial conditions are binding only for the innovative entrepreneurs, whose methods of production are not dominant and hence they need to borrow from banks to kickstart their production. Through this device, our model offers an explanation of the technological lock-in experienced by a small, open economy that takes international prices as given.
Keywords: F37; F31; E7; 330; Foreign Exchange Policy; Currency Mismatches; Structural Change